2019
DOI: 10.1016/s0140-6736(19)30622-1
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and infant health outcomes at 9 months of age in the Gaza Strip: a cross-sectional randomised trial

Abstract: Background There are limited studies about optimal duration and benefits of breastfeeding-and in particular, exclusive breastfeeding-on infant health and growth in the occupied Palestinian territory. This study aimed to evaluate the effect of exclusive breastfeeding on the health of infants in the Gaza Strip (at age 9 months), in terms of anthropometric measurements, growth, and morbidity. Methods This study targeted mothers with infants attending primary health centres for vaccination at 9 months of age. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For infants with Bifidobacterium longum subspecies longum present in their gut microbiotas, stool samples collected from their mothers at 6 weeks post-partum also contained that species. This is potentially important, as breastfed infants have lower risk for atopic disease, diarrhetic episodes, and childhood obesity [ 21 , 22 ], which may be related to specific bacterial taxa present early in life. This work can inform future trials to answer questions about the impact of lactation status on maternal gut microbiota and health outcomes for maternal/infant dyads.…”
Section: Resultsmentioning
confidence: 99%
“…For infants with Bifidobacterium longum subspecies longum present in their gut microbiotas, stool samples collected from their mothers at 6 weeks post-partum also contained that species. This is potentially important, as breastfed infants have lower risk for atopic disease, diarrhetic episodes, and childhood obesity [ 21 , 22 ], which may be related to specific bacterial taxa present early in life. This work can inform future trials to answer questions about the impact of lactation status on maternal gut microbiota and health outcomes for maternal/infant dyads.…”
Section: Resultsmentioning
confidence: 99%
“…Women who breastfeed are more likely to experience a reduction in risk for Type 2 diabetes and reproductive cancers (Chowdhury et al, 2015). For infants, breastfeeding is associated with a decreased risk of various infections, atopic disease, childhood obesity, and diarrhea (Dieterich et al, 2013; Horta & Victora, 2013; Naser et al, 2019). Although the mechanisms behind these results have yet to be adequately described, the recent work of several groups suggested that the infant gut microbiota may be one conduit through which breastfeeding exerts its protective influence against the subsequent development of atopy and obesity (Dreyer & Liebl, 2018; van den Elsen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%